Improved characteristic of load current of cascaded-flux compression generator / M. Jafarifar, B. Rezaeealam and A.Mir - Jafarifar, M.; Rezaeelam, B.; Mir, A. (UiTM Press, 2018)
One of the main problem of Cascaded-Helical Magnetic Flux Compression Generators (Cascaded-HFCG) is the returned energy from second stage winding to first stage winding after starting of second stage operation. Since there is no electrical connection between first stage winding and the load of the generator, so a great part of energy doesn't reach to the load and losts. This energy loss cause to decrease in generator efficiency and has a great impact on output characteristic of the generator. In this paper, an approach is proposed to minimize returned energy and to improve the output characteristic of a Cascaded-HFCG. The approach is based on time-varying primary winding of dynamic transformer and addition of a gradually incremental resistance in series with the first stage winding. In order to verificate the ability of the proposed approach, a computer code is programed based on a simple model of the generator and a Cascaded-HFCG is simulated for two cases: first case for the conventional generator and the other for the proposed approach. It is demonstrated that for the proposed approach, the output current has a greater value, consequently the current gain of the generator becomes better. The comparison between output currents for two cases shows that the rise-time of output current becomes smaller for the case of proposed approach.